2013
DOI: 10.1111/bjd.12437
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experience and psychometric properties of the Children's Dermatology Life Quality Index (CDLQI), 1995-2012

Abstract: The Children's Dermatology Life Quality Index (CDLQI) is a widely used questionnaire to measure the quality of life of children aged from 4 to 16 years. The purpose of this review is to summarize all published data regarding the clinical experience of the CDLQI and its psychometric properties as a single reference source for potential users. A literature search was carried out to identify all articles describing the use of the CDLQI from 1995 to November 2012. One hundred and six articles were identified, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
111
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(117 citation statements)
references
References 110 publications
(105 reference statements)
3
111
0
3
Order By: Relevance
“…Only a few studies have examined the correlation between the Objective SCORAD and the QoL in children <4 years old using the IDQoL, and the conclusions of those studies are conflicting [25,26,27,28,38,39]. We found that the subjective QoL scores of the children were positively correlated with the objective severity assessments of AD when using the Objective SCORAD, with a significant and good correlation in both the older and the younger age group.…”
Section: Discussionmentioning
confidence: 72%
“…Only a few studies have examined the correlation between the Objective SCORAD and the QoL in children <4 years old using the IDQoL, and the conclusions of those studies are conflicting [25,26,27,28,38,39]. We found that the subjective QoL scores of the children were positively correlated with the objective severity assessments of AD when using the Objective SCORAD, with a significant and good correlation in both the older and the younger age group.…”
Section: Discussionmentioning
confidence: 72%
“…In order to allow interpretation of the СDLQI scores a banding system was validated [17]. The CDLQI has been translated into different languages and used in many studies [18]. It remains the only dermatology-specific QoL instrument for this age group.…”
Section: Hrqol Assessment In Children With Skin Diseasesmentioning
confidence: 99%
“…The scoring for each question is "Very much"[Score = 3], "Quite a lot" [2], "Only a little" [1], "Not at all"[0], "Blank"[0], and Q7 -"prevented school" [3]. The 10 individual question scores are summed to provide a total CDLQI score; the maximum possible score is 30, indicating maximum impact on QoL.…”
Section: Cdlqi Scoring Algorithmmentioning
confidence: 99%
“…Figure 2 highlights the QoL impact severity bands (4). Six studies describing cross cultural adaptations and validation of the CDLQI were identified by Salek et al (3) and summarised in the Table 6 of their detailed review of CDLQI usage.…”
Section: Cdlqi Scores By Conditionmentioning
confidence: 99%
See 1 more Smart Citation